Color assessment in dental prostheses: the use of smartphones as process tools - Albert, Charles Jourdan; da Silva, Elielson Nobrega; Penteado, Marcela Moreira; de Lima, Dimas Renó; Kimpara, Estevão Tomomitsu; Uemura, Eduardo Shigueyuki (Brazilian Dental Science, 2019)
Accurate color selection of direct or indirect dental restorations is a subjective task. Mobile phones are tools that may minimize color assessment errors. Objective: To use photographs taken with smartphones to guide the dental surgeon in choosing the right color in oral rehabilitation. Material and Methods: A tooth was photographed for color assessment and the VITA Toothguide 3D-MASTER® shade guide was used. Photographs were submitted to an image editing software for full saturation removal. Images of the tooth and scale in black and white were compared. Results: This method allowed to select the tooth’s value, which is considered the most subjective dimension in color choice. Conclusion: Although it is an auxiliary and complementary method to traditional methods, smartphones are tools capable of reducing the range of color possibilities and minimizing possible failures. Keywords Color; Photograph; Smartphone.